Spectroscopic investigations on the interaction between cadmium telluride semiconductor nanoparticle and bovine alkaline phosphatase. Issue 2 (7th February 2019) - Babaknejad, Nasim; Shareghi, Behzad; Saboury, Ali Akbar
Abstract: The interaction of enzymes with nanoparticles is important in the field of biotechnology and medicine. Due to the various uses of cadmium telluride nanoparticle in protein science, biotechnology and biophysical chemistry, drug delivery, and cellular imaging, study of this nanoparticle interaction with protein seems to be necessary. Therefore, the interaction between cadmium telluride semiconductor nanoparticle and bovine alkaline phosphatase, a clinical marker enzyme, were investigated by assaying kinetic parameters and fluorescence absorption, UV–vis absorption spectra, and circular dichroism spectroscopic techniques. Obtained results showed that cadmium telluride nanoparticle could quench the fluorescence signal of bovine alkaline phosphatase effectively with a static quenching mechanism. Moreover, the binding of cadmium telluride nanoparticle to the enzyme was spontaneous and van der Waals and hydrogen bonding forces played a key role in the complex stabilization. Circular dichroism spectra measurements indicated that cadmium telluride nanoparticle decreased α-helical content and increased the β-sheet structure of bovine alkaline phosphatase. These findings suggest that cadmium telluride nanoparticle changes the structure and activity of bovine alkaline phosphatase.